What Is a Nonresponder? A Qualitative Analysis of Nonresponse to a Behavioral Intervention. Issue 2 (May 2019) - Nehrig, Nicole; Gillooly, Sara; Abraham, Karen; Shifrin, Maria; Chen, Cory K.
Abstract: This study used qualitative methods to understand reasons for treatment nonresponse following a behavioral intervention for family caregivers of people with dementia. Caregivers and interventionists completed semistructured interviews about their experience of the treatment after completing a course of Resources for Enhancing Alzheimer's Caregiver Health in VA (REACH VA). Treatment response from the 22 caregivers who completed the 12-session treatment was assessed using pre- to posttreatment change scores on measures of depression and caregiver burden. Interviews from the 14 nonresponder caregiver/interventionist dyads (28 total) were analyzed qualitatively to identify caregiver factors that negatively impacted improvement in depression and caregiver burden, such as emotional processing difficulties, wanting more support than structure, and limited support/difficulty asking for help. Ways nonresponders benefited from REACH VA beyond improvement on self-report symptom measures were also identified and included learning to problem solve more effectively, feeling understood and supported by another, and taking a different perspective on caregiving. The benefits of using qualitative methods to assess the experience of treatment nonresponders and identify individuals who may benefit from additional treatment or a different approach are discussed. Highlights: Nonresponders identified meaningful improvements following treatment. Caregivers and interventionists identified contributing factors to nonresponse. Qualitative methods are useful for determining outcome variables besides symptoms.